Prospective mixed-methods study of patients undergoing relaparotomy (ReLap study; DRKS00013001) - Tran, Dinh Thien-An; Dörr-Harim, Colette; Hüttner, Felix; Harnoß, Julian-Camill; Knebel, Phillip; Schneider, Martin; Büchler, Markus W.; Diener, Markus K.; Probst, Pascal (International journal of surgery protocols, 2018)
Background: Patients undergoing relaparotomies are underrepresented in clinical trials. Standard of care, relative outcomes compared to primary laparotomy, and the ideal fascial closure technique are unknown. Objective: The ReLap study has three objectives: First, to determine standard of care and gain evidence of intra-/postoperative outcomes for patients undergoing relaparotomy compared to patients undergoing primary laparotomy. Second, to gain evidence of an association between biomarkers and adhesion grade in a clinical-translational approach in patients undergoing relaparotomy or primary laparotomy. Third, to gain evidence of the feasibility and comparative effectiveness of fascial closure after relaparotomy using the small stitches technique with Monomax 2-0 versus the large stitches technique with PDS 1 loop. Methods: The ReLap study is a monocentric, prospective, mixed-methods, exploratory study with three steps: health care research, translational research, and randomized controlled trial. All patients scheduled for elective laparotomies or relaparotomies at the University of Heidelberg will be screened for eligibility. There will be five study visits during the hospital stay and one study visit one year after surgery. The clinical course will be followed and outcomes necessary to answer the study objectives will be captured prospectively. Relaparotomy patients eligible for closure with the small and large stitches technique will be randomized intraoperatively to one technique. Discussion: The ReLap study will bridge a significant knowledge gap regarding patients undergoing relaparotomy. Differences in the standard of care between relaparotomies and primary laparotomies will be determined. The relation between biomarkers and manifestation of adhesions will be explored and evidence for the comparative effectiveness of fascial closure after relaparotomy will be gained.